Natural polymer composite from oil palm decanter cake (OPDC) / Aiman Ahmad Taridi - Ahmad Taridi, Aiman (Faculty of Plantation and Agrotechnology, 2016)
This project was conducted to develop the natural polymer composite (NPC) from oil palm decanter cake (OPDC). OPDC is one of the wastes at oil palm mill with solid form that has been taken from FELDA Trolak Palm Oil Mill, Perak. This solid OPDC was treated with several types of treatment and chemical. OPDC was treated with alkaline treatment (NaOH), acid treatment (H2S04), and peroxide treatment (H202). OPDC with different percentage (5%,10%,15%) then was extruded into rectangular shape with polypropylene using twin screw extruder machine (TSE-16 PRISM, USA) and hot press mould machine. The sample then was tested with several tests to gain primary data of mechanical and physical properties of the NPC product.